2021
DOI: 10.1111/jth.15435
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes among patients with cancer and incidental or symptomatic venous thromboembolism: A systematic review and meta‐analysis

Abstract: Summary Background Patients with cancer have an increased risk of venous thromboembolism (VTE) and it is commonly detected incidentally. The outcomes and optimal management for patients with cancer and incidental VTE remain debated. Objectives We conducted a systematic review and meta‐analysis to evaluate the outcomes in patients with cancer and incidentally detected VTE compared to those with symptomatic events. Patients/Methods We searched the electronic databases and included randomized controlled trials (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 47 publications
(138 reference statements)
2
17
0
5
Order By: Relevance
“…Although patients with incidental VTE (i.e., asymptomatic thrombosis found on screening imaging tests) were not included in the RCTs of LMWH vs. VKA [ 8 , 9 , 24 , 25 , 26 ], between 20% and 53% of patients included in the RCTs of DOACs vs. LMWH had incidental VTE at baseline [ 16 , 17 , 18 ]. Although the rate of recurrent VTE is lower in patients with incidental VTE compared to those with symptomatic events (RR: 0.62; 95% CI 0.44 to 0.87), the rate of recurrent events despite anticoagulation remains high [ 31 ]. For example, the results of a subanalysis of patients with incidental vs. symptomatic VTE in the Hokusai-VTE Cancer trial found recurrent VTE occurred in 7.9% of patients with incidental VTE as compared to 10.9% of those with symptomatic VTE [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although patients with incidental VTE (i.e., asymptomatic thrombosis found on screening imaging tests) were not included in the RCTs of LMWH vs. VKA [ 8 , 9 , 24 , 25 , 26 ], between 20% and 53% of patients included in the RCTs of DOACs vs. LMWH had incidental VTE at baseline [ 16 , 17 , 18 ]. Although the rate of recurrent VTE is lower in patients with incidental VTE compared to those with symptomatic events (RR: 0.62; 95% CI 0.44 to 0.87), the rate of recurrent events despite anticoagulation remains high [ 31 ]. For example, the results of a subanalysis of patients with incidental vs. symptomatic VTE in the Hokusai-VTE Cancer trial found recurrent VTE occurred in 7.9% of patients with incidental VTE as compared to 10.9% of those with symptomatic VTE [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of patients with incidental cancer-associated VTE varied from 3.8% to 80.8%. In 16 of the 20 observational studies, the overall mortality was lower in patients with incidental events [4].…”
Section: Incidental Vs Suspectedmentioning
confidence: 98%
“…To summarize the currently available literature, our group recently conducted a systematic review and meta-analysis to evaluate outcomes in cancer patients with incidentally detected VTE compared to those with suspected events [4]. Our eligibility criteria included studies that enrolled adult patients with cancer-associated VTE and reported the efficacy and safety of anticoagulation in patients with incidental and symptomatic index events.…”
Section: Incidental Vs Suspectedmentioning
confidence: 99%
See 2 more Smart Citations